Fixed point results for ℑ-Contractions in JS-generalized metric spaces with an application - Bilal Iqbal; Naeem Saleem; Maggie Aphane; Asima Razzaque (PLoS ONE, 2025)
The goal of this work is to establish ℑ-contractions and to show some novel fixed point theorems for these contractive conditions in the setting of generalized metric spaces in the sense of Jleli and Samet. Finally, using proven fixed point results, an existence result for a solution of the RLC circuit’s current differential equation is established.